The identity of the faces: animated illustration inspired by Yvette Chua and Fernanda Dias - Mariana Muñoz Gonzalez; Victor Reyes Espino (ХНУРЕ, 2022)
As a result of the human need to express their identity, portrait is discovered, one of the pillars of great relevance in art. Since ancient times, ways of representing the human figure have been sought, generating new trends in the form of sculptures or paintings, which led to busts or murals with large portraits of characters, including gods.
Keywords: animated; illustration